2004
DOI: 10.1093/annhyg/meh050
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Local Exhaust Ventilation for Controlling Dust Exposures During Concrete Surface Grinding

Abstract: This study assessed the effectiveness of a commercially available local exhaust ventilation (LEV) system for controlling respirable dust and crystalline silica exposures during concrete grinding activities. Surface grinding was conducted at six commercial building construction sites in Seattle, WA, by cement masons. Time-integrated filter samples and direct reading respirable dust concentrations were collected using a cyclone in line with a direct reading respirable dust monitor. Personal exposure levels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…LEV, particularly on-tool LEV, has proven effective in respirable dust control in concrete grinding and polishing (Akbar-Khanzadeh and Brillhart 2002; Akbar-Khanzadeh et al 2007; Akbar-Khanzadeh et al 2010; Healy et al 2014; Croteau et al 2004; Croteau et al 2002; Echt and Sieber 2002; Flynn and Susi 2003), but the effectiveness of LEV in stone countertop fabrication with or without wet methods is largely uncharacterized. Cooper et al (2015) reported that during engineered stone cutting using a hand-held worm-drive circular saw under controlled conditions, wet cutting with LEV was highly effective, reducing operator exposures by over 90% compared to the usual practice of wet cutting without LEV.…”
Section: Introductionmentioning
confidence: 99%
“…LEV, particularly on-tool LEV, has proven effective in respirable dust control in concrete grinding and polishing (Akbar-Khanzadeh and Brillhart 2002; Akbar-Khanzadeh et al 2007; Akbar-Khanzadeh et al 2010; Healy et al 2014; Croteau et al 2004; Croteau et al 2002; Echt and Sieber 2002; Flynn and Susi 2003), but the effectiveness of LEV in stone countertop fabrication with or without wet methods is largely uncharacterized. Cooper et al (2015) reported that during engineered stone cutting using a hand-held worm-drive circular saw under controlled conditions, wet cutting with LEV was highly effective, reducing operator exposures by over 90% compared to the usual practice of wet cutting without LEV.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, monitoring is performed either by stationary measurements or by personal monitoring, i.e. equipping some of the workers present on site (Croteau et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…LEV is used in industries in order to help reducing workers' exposure to particles at workstations. The use of LEV resulted in an overall exposure reduction of 92% [1]. Figure 1 shows the common elements of LEV system.…”
Section: Introductionmentioning
confidence: 99%